Conflict Management in Handling Extortion Cases in Schools - Zahroh, Kamilatus; Ahmadi, Ahmadi (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
Extortion is a form of intimidation or extortion involving threats and violence, and is one of the main problems that occur in the school environment. This study aims to determine the factors causing extortion conflicts and the strategies implemented by the principal. This study uses a qualitative approach with a case study method. Data were collected through interviews, direct observation, and documentation. The subjects of this study were the principal, teachers, and students who were perpetrators or victims in extortion cases. Data validity was guaranteed through triangulation of techniques and sources. The data obtained were then analyzed through condensation, data presentation, and drawing conclusions. The results of the study showed that the factors causing extortion conflicts were: less supportive social and school environmental conditions, peer influence, and family background, such as ineffective parenting patterns. Meanwhile, the strategies implemented by the principal were: individual and group counseling approaches, strengthening religious values, and conflict management policies such as mediation and sanctions. Individual counseling helps perpetrators understand their impact, while group counseling builds students' awareness of the importance of mutual respect. Strengthening religious values ​​through religious activities, such as Islamic studies and joint prayers, has also succeeded in forming better student character. The study contributes as a reference for schools in handling cases of radicalism or other violence.